Dispensasi Nikah Bagi Anak Dibawah Umur Ditinjau dari Perspektif Kompilasi Hukum Islam Berdasarkan Penetapan Pengadilan Agama Pringsewu (Studi Putusan Nomor : 62/Pdt.P/2020/PA.PRW) - Baharuddin Baharuddin; Risti Dwi Ramasari; Chintia Mutiara Dewi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
The determination of the dispensation for underage marriages is still based on considerations in accordance with the Marriage Law, namely limiting the minimum age of marriage to 19 (nineteen) years for both men and women. This study discusses issues regarding judges' considerations and the legal consequences of determining marriage dispensation for minors based on the Pringsewu Religious Court Decision Number: 62/Pdt.P/2020/PA.PRW. This study uses a normative juridical approach and an empirical juridical approach. Collecting data by field studies and literature studies. Data analysis was carried out in a qualitative juridical manner, namely the analysis was carried out descriptively. The dispensation for underage marriages needs to be tightened in more detail, so that the public is more aware and aware of the more negative impacts than the positive impacts that will arise on children who engage in underage marriages physically, mentally, and socially.